AN INTERPRETIVE METHODOLOGY FOR THE STUDY OF THE SOCIAL MOVEMENTS. BOUNDERIES AND CULTURE. A VISION FROM MEXICO - Villafuerte Valdés, Luis Fernando (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The relation among political and intellectual system and the academic debate had a very narrow link in Mexico, so much that it was determining the debate on the “hegemonic” theories to be used in the academic environment of the country. This is why when the force of the political authoritarian models becomes exhausted, the academic relations are modified and there is the open possibility of incorporating new theories to explain the social process.